Hubungan Resiliensi Akademik dan Stres Akademik pada Mahasiswa Pendidikan Agama Islam - Munawarah Munawarah; Nazwa Salsabilla; Noviani Hidayah; Surawan Surawan (FKIP Universitas Islam Jember, 2026)
This article was written to examine the relationship between academic resilience and academic stress among Islamic Education students at UIN Palangka Raya. This study focuses on the high academic demands that have the potential to cause academic stress among students during the course of their studies. To address this issue, the study employs the theoretical framework of resilience proposed by Howard and Johnson, while the theory of academic stress is based on Bernadette M. Gadzella’s work. Research data were collected from 51 respondents using purposive sampling and analyzed quantitatively via Spearman’s rho correlation test. The results reveal a strong positive correlation between academic resilience and academic stress (r = 0.584; p = 0.000). These findings warrant further research into the protective functions of academic resilience.